The Poem “Ritratto di donna” by J. Brodsky: Context and Interpretations - Автухович, Татьяна (Literatūra, 2016)
The article offers an interpretation of the poem of I. Brodsky “Ritratto di Donna”, based on the establishment of contextual links with the picture by the great Italian Renaissance painter Raphael “La Donna Velata (The woman with the veil)” and Brodsky’s essay “Altra Ego” (1990). It is argued that the poem by Brodsky is an “improper ecphrasis” whose purpose is not the description of works of art. This poem is the metaphysical meditation about the essence of art, about the relation between daily life and Being in the artistic creativity.
Keywords: Brodsky; contextual links; “La Donna Velata” by Raphael; ecphrasis; essence of art